ANALISIS DAN PENANGANAN PERILAKU AGRESIF SISWA MELALUI BIMBINGAN PRIBADI TEKNIK MODELLING (STUDI KASUS PADA SISWA KELAS VIII NEGERI 4 BAUBAU) - Taherong, Rosmawati; Melisa, Melisa (JEC (Jurnal Edukasi Cendekia), 2019)
This study aims to describe the Analysis and Handling of Student Aggressive Behavior through Personal Guidance of Modeling Techniques (Case Studies in Class VIII Students of SMP Negeri 4 Baubau) for the 2019/2020 Academic Year. This research approach is a qualitative descriptive approach with a case study method. This study consisted of 1 subject from several of the same sources. The data sources were from the guidance and counseling teachers, subject teachers, homeroom teachers, peers, and parents. Data collection methods used observation, interviews and triangulation with the stages of problem identification, diagnosis, prognosis, treatment and follow-up. The results showed the condition of students before the counseling process was carried out, namely, there was a change from initially still often engaging in aggressive behavior to sometimes, even not being done at all. As for the comparison before the counseling process and after the counseling process using individual counseling services (case study) Modeling techniques are stated to be successful in reducing students' aggressive behavior.